PENGARUH PENGGUNAAN METODE PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS XI DI MAN 2 PONTIANAK TAHUN AJARAN 2025/2026 - Putri Aulia, Nabila; Imran, Yusida; Alias, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the Mind Mapping learning method on student learning outcomes in the Islamic Cultural History course for 11th-grade students at MAN 2 Pontianak during the 2025/2026 academic year. The research method used was a quantitative study with a quasi-experimental design. The population in this study comprised all 11th-grade students at MAN 2 Pontianak, and the research sample consisted of Class 11C as the experimental class and Class 11G as the control class. Data collection was conducted through tests divided into two categories: a pretest, administered to students before the intervention, and a posttest, administered after the intervention. The data analysis technique used was the independent samples t-test because the data used in the test—the posttest scores of the experimental and control groups—were normally distributed. In the experimental group, the pretest mean score of 47.67 increased to 83.00 on the posttest. Meanwhile, in the control class, the average pretest score of 50.39 increased to 77.61 on the posttest. The results of the hypothesis test yielded a significance value (Sig., 2-tailed) of 0.043 < 0.05, so H₀ was rejected and H₁ was accepted. This indicates that the use of the Mind Mapping learning method has an effect on student learning outcomes in the Islamic Cultural History course for 11th-grade students at MAN 2 Pontianak.